2014
DOI: 10.1186/1471-2474-15-110
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of tourniquet assisted total knee arthroplasty on patient-reported and performance-based physical function: a randomized controlled trial protocol

Abstract: BackgroundSurgical treatment of osteoarthritis with total knee arthroplasty (TKA) usually takes place in a complete bloodless field using a tourniquet. However, doing the surgery without a tourniquet may reduce muscle damage, post-surgery pain and led to improved functional rehabilitation and mobilization.Methods/DesignA prospective, blinded, parallel-group, controlled superiority trial, with balanced randomization [1:1]. Patients aged 50 or older eligible for primary TKA for osteoarthritis will be consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…However, this meta-analysis found no significant between-group differences in total or hidden blood loss, although the total blood loss was more, and the hidden blood loss was less, in the closed drainage group. Clinically, the postoperative bleeding is thought to occur during the early stage after surgery, and as a result, many studies have theorised that postoperative bleeding might be decreased by the temporary clamping of drains postoperatively [ 24 , 25 ], the use of a tourniquet intraoperatively [ 26 , 27 ], and/or intravenous and/or local use of tranexamic acid perioperatively [ 28 ], which is discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…However, this meta-analysis found no significant between-group differences in total or hidden blood loss, although the total blood loss was more, and the hidden blood loss was less, in the closed drainage group. Clinically, the postoperative bleeding is thought to occur during the early stage after surgery, and as a result, many studies have theorised that postoperative bleeding might be decreased by the temporary clamping of drains postoperatively [ 24 , 25 ], the use of a tourniquet intraoperatively [ 26 , 27 ], and/or intravenous and/or local use of tranexamic acid perioperatively [ 28 ], which is discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Cushing's inspiration for pneumatic tourniquet came from sphygmomanometer system. It is now more than a century that surgeons use pneumatic tourniquet to manage intraoperative bleeding [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, electromyographic alterations in the quadriceps muscle were also reported after using tourniquet for knee surgeries [10]. In addition, Lohmann-Jensen et al reported that patients who underwent no-tourniquet total knee arthroplasty were able to start rehabilitation exercises faster than patients who received tourniquet-assisted total knee arthroplasty and thus, they were able to use their newly-transplanted knee more confidently, experienced fewer immobility-related complications, and expressed higher satisfaction with medical and care services [9].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumatic tourniquets, first proposed in 1904 by Cashing, contain cuffs, which encircle the limb and are inflated with compressed gas (3,4). Tourniquets have been used for a century by surgeons for operations on lower limbs, with higher pressure than systolic blood pressure (5).…”
Section: Introductionmentioning
confidence: 99%